Two essays on Colorado State University's Wheat Breeding and Genetics Program - Mortenson, Ryan A., author; Pendell, Dustin L., advisor; Parsons, Jay, advisor; Haley, Scott D., committee member (Colorado State University. Libraries, 2012)
Colorado State University's Wheat Breeding and Genetics Program is nearing its' 50th anniversary and has had a large role in providing a vehicle of research for increasing wheat yields in Colorado. During this research process, a database has been compiled of the results of wheat variety experiments held on test plots statewide. The intent of this thesis is to demonstrate additional uses of the data collected by CSU's Wheat Breeding and Genetics Program and the Crop Variety Testing Program. The first essay is an evaluation of the economic impacts that the breeding program has had on wheat yields attributable to the genetic improvement of wheat varieties. Regression analysis is used to estimate and track the genetic improvement that occurs with each newly released wheat variety. The analysis is followed by a monetization of the estimated benefits produced by the program as a result of the increase in wheat yields. Costs of running the program are also discussed. Borrowing from finance literature, the second essay utilizes the Colorado Wheat Variety Database to generate a portfolio of wheat varieties that would result in minimizing variation while maximizing wheat yields to help producers lower their overall risk levels. Portfolio theory is widely used to select investments in the financial world. The intended application of this study is to aid wheat producers in their selection of wheat varieties.
Keywords: economic impacts; wheat breeding; risk; portfolio theory